DOM evolution and microbial function during anaerobic digestion under supplementing Fenton sludge: A comparative study - Minhui Cai; Ruize Xia; Zheng Wang; Jun Li; Qing Zhou; Yan Li; Wentao Li; Aimin Li (Journal of Environmental Chemical Engineering, 2026)

CHBP-loaded mesoporous polydopamine nanoparticles attenuate neuroinflammation and reprogram microglia-neuron crosstalk for spinal cord injury repair - Linyi Xiang; Jiacheng Zhang; Yuzhe Wu; Jingwei Shi; Yun Shu; Ruize Miu; Jiayi Zhao; Junsheng Zhu; Zhichao Tao; Yibo Geng; Haojie Zhang; Zhenglin Li; et al. (Chemical Engineering Journal, 2026)

Revealing the interaction between the internal microbiota of Daqu pests and Daqu microbes based on metagenomics technology - Yaao Zhou; Chunxue Zhang; Ao Zhang; Mengjia Zhang; Jiangfan Liu; Ruize Zhang; Fanfan Lang; Jia Song; Yu Zheng; Min Wang (Food Bioscience, 2026)

Discovery and Optimisation of Novel Bombinin-Derived Peptides from Bombina variegata against Staphylococcus aureus - Jiachen Liu; Keyi Yao; Ruize Sun; Xiaonan Ma; Chengbang Ma; Xiaoling Chen; Yangyang Jiang; Tao Wang; Tianbao Chen; Chris Shaw; Mei Zhou; Lei Wang (Probiotics and Antimicrobial Proteins, 2026)
Amphibian skin-secreted antimicrobial peptides (AMPs) have garnered significant attention for their excellent biological activity and low propensity for drug resistance over the past 40 years. Bombinins and bombinin H, two classes of AMPs isolated from the skin secretions of Bombina species, demonstrate strong antimicrobial activity against broad-spectrum microorganisms. In this study, two novel peptides, bombinin-like peptide 7S and bombinin-H2L, were identified from the toad, Bombina variegata . While both peptides exhibited broad-spectrum antimicrobial activity, they also showed relatively high cytotoxicity. To explore the structure–activity relationship and enhance therapeutic potential, bombinin-H2L, which displayed stronger average antimicrobial activity, was used as a template. With the aid of bioinformatics analysis, a series of bombinin-H2L analogues were designed by increasing the net positive charges and/or adjusting the amphiphilicity of the parent peptide. Among these analogues, [Arg 8, 15 ]BH2L and [Lys 7, 8 ]BH2L demonstrated high therapeutic efficacy and specificity toward clinically isolated, drug-resistant Staphylococcus aureus strains in both in vitro and ex vivo tests. Their notable biosafety profiles, sensitivity to diverse environments, and ability to disrupt biofilms highlight their potential for further development. Additionally, studies on the mechanism of [Arg 8, 15 ]BH2L and [Lys 7, 8 ]BH2L revealed a membrane-targeted antimicrobial mechanism, with its antibacterial function exerted by disrupting the integrity of bacterial membranes. These findings provide valuable insights into structural modifications of bombinin H peptides for enhanced activity, and [Arg 8, 15 ]BH2L and [Lys 7, 8 ]BH2L have the potential as promising candidates for novel antibacterial agents in treated bacterial skin infections.

The multi-stages Sn mineralization process in the Xianghualing orefield: Constraints from cassiterite and vesuvianite U Pb geochronology - Zhang Dexian; Zhou Jialing; Fang Ruize; Xiao Dian; Hu Ziqi (Geochemistry, 2025)

An assessment of the levels of emerging and traditional organophosphate ester flame retardants in dairy products in China and their combined dietary risks - Ruize Zhou; Jianqiang Geng; Jie Jiang; Bing Shao; Li Lin; Baolong Wang; Yantao Wu; Wei Li (Food and Chemical Toxicology, 2025)

Influence of low-temperature pyrolysis pretreatment on the co-combustion performance of coal and waste polyvinyl chloride/tire - Mengli Zhou; Yang Xu; Guangqian Luo; Ruize Sun; Renjie Zou; Chunhui Sun; Xian Li; Hong Yao (Fuel, 2024)

Research on mercury re-release model in wet flue gas desulfurization (WFGD) in coal-fired power plants - Ruize Sun; Mingyu Yu; Guangqian Luo; Li Wang; Mengli Zhou; Xinpei Lu; Xian Li; Hong Yao (Chemical Engineering Journal, 2024)

Contamination of dairy products with tris(2,4-di-tert-butylphenyl) phosphite and implications for human exposure - Ruize Zhou; Jianqiang Geng; Jie Jiang; Bing Shao; Li Lin; Tongna Mu; Baolong Wang; Ting Liu (Food Chemistry, 2024)

Emerging organophosphite and organophosphate esters in takeaway food and the implications for human exposure - Ruize Zhou; Jianqiang Geng; Jie Jiang; Bing Shao; Baolong Wang; Yu Wang; Minggang Li (Environmental Science and Pollution Research, 2024)

Occurrence and migration of organophosphite and organophosphate esters into food simulants from single-use food packaging in China - Ruize Zhou; Jianqiang Geng; Jie Jiang; Li Lin; Jing Zhang; Yunjia Yang; Xiaojun Wang; Yumin Niu; Bing Shao (Environmental Pollution, 2023)